Efektivitas Media Komik Berbasis Karakter Terhadap Hasil Belajar Submateri Pelestarian Lingkungan di MAN 1 Kubu Raya - Lilis Indriyani; Kurnia Ningsih; Anisyah Yuniarti (Jurnal Penelitian Pendidikan IPA, 2024)
The utilization of learning media is one of the alternatives to increase knowledge for students, especially biology learning. In addition, student character can be improved through media in which there is character insertion. Thus, an innovative learning media is needed to improve knowledge and character through character-based comics on environmental conservation submaterial. This research method is a quantitative experiment, with a pretest-posttest control group research design. The sample consisted of 28 control class students and 30 experimental class students. The instruments were 20 multiple choice questions and 22 character questionnaire statements. Data analysis techniques include knowledge assessment measured using the Independent samples t-test formula. The results of data analysis showed that the knowledge of experimental class students increased significantly, the learning outcomes in the experimental class showed a higher average of 86.67 while the control class was 74.46, the average difference in learning outcomes between experimental and control classes was evidenced by the independent samples t-test test value of 0.00 <0.05, and student character showed a percentage of 81.44% in the excellent category. It is concluded that character-based comic media on environmental conservation submaterial can help improve cognitive learning outcomes and student character.